Pooled subsidence records from numerous wells reveal variations in pre-break-up rifting along the proximal domains of the Iberia–Newfoundland continental margins. (22nd November 2018) - Spooner, Cameron; Stephenson, Randell; Butler, Robert W.H.
Abstract: The Iberia–Newfoundland continental margin is one of the most-studied conjugate margins in the world. However, many unknowns remain regarding the nature of rifting preceding its break-up. We analyse a large dataset of tectonic subsidence curves, created from publicly available well data, to show spatial and temporal trends of rifting in the proximal domains of the margin. We develop a novel methodology of bulk averaging tectonic subsidence curves that can be applied on any conjugate margin with a similar spread of well data. The method does not rely on the existence of conjugate, deep seismic profiles and, specifically, attempts to forego the risk of quantitative bias derived from localized anomalies and uncertain stratigraphic dating and correlation. Results for the Iberia–Newfoundland margin show that active rift-driven tectonic subsidence occurred in the Central segment of the conjugate margin from c. 227 Ma (early Norian) to c. 152.1 Ma (early Tithonian), in the southern segment from c. 208.5 Ma (early Rhaetian) to c. 152.1 Ma (early Tithonian) and in the northern segment from c. 201.3 Ma (early Hettangian) to c. 132.9 Ma (early Hauterivian). This indicates that rifting in the stretching phase of the proximal domain of the Iberia–Newfoundland margin does not mirror hyperextended domain rifting trends (south to north) that ultimately led to break-up. The insights into broad-scale three-dimensional spatial and temporal trends, produced using the novel methodology presented in this paper, provide added value for interpretation of the development of passive margins, and new constraints for modelling of the formation of conjugate margins.